Successful pregnancy outcome in two patients with Pyonephrosis treated with percutaneous Nephrostomy - Shullai, Wansalan Karu; Agarwal, Manika; Reddy, Kalyani; Singh, A S (Asian Journal of Medical Sciences, 2015)
Urinary tract infections in pregnancy are common in the form of cystitis and pyelonephritis. Rarely patients may have pyonephrosis. Some of these patients may respond to antibiotic therapy. However those who do not, can be treated by drainage of pus under USG guided percutaneous nephrostomy. Though invasive procedures are generally avoided in pregnancy, however if required, it should be undertaken judiciously or the primary condition may aggravate which may lead to adverse pregnancy outcome. These cases are being presented to highlight that appropriate intervention in the form of percutaneous nephrostomy, is associated with favorable maternal and fetal outcome. Asian Journal of Medical Sciences Vol.7(2) 2015 109-111